Approaches to designing micro‐solenoidal RF probes for 14 T MRI studies of millimeter‐range sized objects. Issue 4 (24th January 2017) - Seifi, Bahram; Semouchkina, Elena; Lanagan, Michael; Neuberger, Thomas
Abstract: Full‐wave electromagnetic simulations have been employed to analyze the design approaches that allow for solving the problems preventing inductive performance of micro‐solenoidal RF probes and formation of strong and homogeneous magnetic fields inside probes at the studies of millimeter‐range sized objects in 14 T MRI scanners. In particular, the effects of non‐uniform coil wrapping on field homogeneity inside extended coils and of partitioning the coils by dielectric separators on coil self‐resonances have been investigated. The possibility to utilize tunable C‐C matching circuits with the coils and to mitigate the effects of sample insertion on the probe resonance frequency has been demonstrated. Challenges of coil fabrication have been also addressed.